Artroplastia total de joelho assistida por computador - Luiz Fernando Machado Soares (2010)
Osteoarthritis of the knee (gonarthrosis) is a joint disease resulting from various pathological processes that lead to cartilage degradation and still not fully understood. There are several proposals for its treatment, being the total knee arthroplasty an established and reliable option in many cases (14). The total knee arthroplasty evolved considerably in recent years. The development of surgical technique, reliability and durability of the materials are the main reasons for this. Even though this development, the causes of reoperation, especially the early ones, occur in 29% of the cases, at the expenses of poor positioning of implants (23). Recently, surgeons, engineers and computer technicians have joined forces to develop new methods for improving the placement of components in total knee arthroplasty. The aim of this study was to evaluate one of these systems. We studied 20 patients who underwent computerassisted total knee arthroplasty from February 2002 to February 2004, in the Department of Knee Surgery, Hôpital de La Croix Rousse - Université Claude Bernard Lyon 1 (Lyon, France ). Radiological measurements were assessed preand postoperatively, as well as evaluation of the mechanical axes for the affected limb and positioning of the implants. The averages of radiological findings before surgery were: ATFM, 175.45 °; AFm, 90.6°, ATM, 87.7 ° and tibial slope, 6.75 °. The averages of radiological findings in the postoperative period were: ATFM, 179.7 °; AFm, 89.1 °, ATM, 90.0 °, posterior tibial slope, 0.3 °; flexed deformity of the femoral component, 1.3 °. The perioperative and postoperative bleeding was not superior to the classical procedure. The mean tourniquet time was 109.5 minutes (min 80, max 130). In no case the conversion to the conventional technique was necessary. In one patient, limb alignment was kept in a residual valgus of 4° to obtain satisfactory ligament balance which may have interfered with the unintended outcome of postoperative AFm. All other results demonstrated that the technique is reliable